#TITLE_ALTERNATIVE# - B. V. B. SIMORANGKIR (NIM : 13206203); Pembimbing, : Dr. Achmad Munir, ROY
In the design of Stepped Frequency Continuous Wave Ã‚Â– Ground Penetrating Radar (SFCWGPR), there is always a trade-off between spatial resolution and depth of penetration which depend on its application. Lower frequency gives deeper penetration, whilst higher frequency gives better resolution. So, the problem is we always need different antena for different GPR applications. Therefore, producing an antena that can be applied for several level penetrations, resolutions, moreover can answer the need of bandwidth of the system using narrow period pulse like GPR will be something beneficial. In this work, a novel compact UWB antena within a frequency of 50-5000 MHz for SFCWGPR application is proposed as the solution. The antena design is an octopus-type microstrip antena, named according to its shape, which is a modification of resistive loaded T-shape monopole antena by adding four abrupt transitions on its shape and circular patch under it as octopus head. Resistive loading is used in the end of modified T-shape monopole to enhance the bandwidth of the antena and also to suppress the ringing level which is important to get the better resolution of GPR system. Four abrupt transitions and circular patch are effective to increase gain and radiation efficiency of the antena. U-shape ground plane is used to improve impedance matching after adding the circular patch. A 50Ω microstip line is applied for feeding the antena. Cavity is also designed to equip the antena to get the unidirectional radiation pattern and improve gain. Parametric study about arms, head, U-shape ground plane dimensions, resistive load value, and cavity is carried out to investigate the influence of each parameter to antena characteristic. Several simulations using 3D simulator software has been done in order to get the optimum design of the antena. The antena is then deployed on 72.8 x 60 mm2 FR-4 Epoxy substrate with dielectric constant of 4.3 and thickness of 1.6 mm. Measurement is carried out to validate the return loss, VSWR, gain, and radiation pattern result obtained form simulation and also ringing level of the antena. From simulations and measurement, we get the optimum design of octopus-type antena with 4 abrupt transitions and U-shape ground plane which works well (VSWR < 2) in the frequency band 50 Ã‚Â– 5000 MHz and also has a low ringing level.